2011
DOI: 10.1007/s11434-011-4546-4
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of the transcriptome of Porphyra yezoensis with Solexa sequencing technology

Abstract: With high-throughput Solexa sequencing technology, we profiled Porphyra yezoensis transcriptomes from 8 different samples. More than 1200 megabases from 13333334 quality paired-end reads were generated, which were assembled into 31538 unigenes. Blast analysis showed that 56.7% unigenes were novel, which represented the specific genes of Porphyra and/or rhodophytes. Several hundreds of unigenes related to stress tolerance were discovered, including genes related to desiccation-(211) and high light-tolerance (31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 48 publications
2
29
0
Order By: Relevance
“…Dinucleotide repeats (DiNR) and hexanucleotide repeats (HexaNR) were approximately 1.3 and 4.4 %, respectively. Previous reports have also shown that TriNRs were most abundantly distributed in the coding sequence of Pyropia and other plants (Choi et al 2013;Yang et al 2011). Among TriNR, GGC was the most common motif, followed by CCG, CGG, GCG, GCC, and CGC.…”
Section: Identification Of Ssrsmentioning
confidence: 79%
See 1 more Smart Citation
“…Dinucleotide repeats (DiNR) and hexanucleotide repeats (HexaNR) were approximately 1.3 and 4.4 %, respectively. Previous reports have also shown that TriNRs were most abundantly distributed in the coding sequence of Pyropia and other plants (Choi et al 2013;Yang et al 2011). Among TriNR, GGC was the most common motif, followed by CCG, CGG, GCG, GCC, and CGC.…”
Section: Identification Of Ssrsmentioning
confidence: 79%
“…With the advent of next-generation sequencing (NGS) methods such as Roche/454 and Illumina/Hi-seq, large-scale transcriptome sequences can be generated economically from a wider range of organisms (Cheung et al 2008;Huang et al 2012;Lister et al 2008;Qin et al 2008). NGS has also been used in marine algae to determine differentially expressed genes (DEG) between different culture conditions, including abiotic stressors (Choi et al 2013;Pearson et al 2010;Yang et al 2011), and for transcriptome characterization of Pyropia and Porphyra (Chan et al 2011(Chan et al , 2012aStiller et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The large number of reads and associated paired-end information that were produced resulted in a relatively high coverage depth (average = 33.56 ×). When these sequences were assembled, we obtained longer Unigenes (mean = 449 bp) than has been reported previously in studies using the same technology; for example, Camellia sinensi s (mean Unigene length = 355 bp) [29], Lycoris sprengeri (385 bp) [30], Porphyra yezoensis (419 bp) [31] and whitefly (clusters = 372 bp; singletons = 265 bp) [27]. The number of assembled Unigenes was 112-fold more than all the Chinese fir sequences that were currently deposited in GenBank (as of March 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This simplifies the identification of transcription start sites, new splicing variants and rare transcripts, and allows allele expression to be monitored [20,21]. Furthermore it allows the direct transcriptome analysis of non-model organisms, and has been successfully applied to non-model organisms recently [22-31]. …”
Section: Introductionmentioning
confidence: 99%
“…changii [51], G . tenuistipitata [60], Porphyra yezoensis [61,67], P . haitanensis [59], Eucheuma denticulatum [74], Furcellaria lumbricalis [52], and Kappaphycus alvarezii [66], possibly indicating a general pattern of expression in red seaweeds.…”
Section: Discussionmentioning
confidence: 99%